Singlet Oxygen Quenching Effect of Andaliman (Zanthoxylum acanthopodium DC.) Extracts in Light-Induced Lipid Oxidation - Edi Suryanto; H Sastrohamidjojo; Sri Raharjo; Tranggono Tranggono (Indonesian Food and Nutrition Progress, 2004)
Addition of andaliman extract has been shown to provide increased protection from lipid oxidation during cooking. Although andaliman extract has reported as an effective antioxidant in autoxidized system, no study have been published on its effects on light-induced oxidation or photosensitized oxidation. The objective of this research is to determine singlet oxygen quenching effects of andaliman extract on erythrosine-sensitized photooxidation of linoleic acid and in palm oil. Freeze dried ground andaliman fruit was sequentially extracted first using hexane, followed by acetone, and finally the residue was extracted by ethanol. Each of these three extracts were added to light-induced lipid peroxidation in a reaction system containing linoleic acid or palm oil with the presence of erythrosine as a photo sensitizer. Upon the exposure of fluorescent light at 4000 lux singlet oxygen is presumably formed from triplet oxygen which initiate the lipid peroxidation process. The sequential extraction of andaliman resulted in ethanolic extract containing phenolic compounds consistently show antioxidative activity presumably through singlet oxygen quenching in light-induced lipid peroxidation in either linoleic acid or RBD palm oil reaction mixture containing erythrosine as a photosensitizer. The andaliman hexane and acetone extracts may contain not only phenolic compounds, but also trace amount of plant pigments which resulted in stronger lipid peroxidation effect than the antioxidative effect of phenolic substances, especially at higher level of addition.